Produção de bioetanol a partir de pedúnculo de caju (Anacardium occidentale L.) por fermentação submersa - Rocha, Maria Valderez Ponte (2010)
Recently, global demand for ethanol fuel has expanded very rapidly, and this should further increase in the near future, almost all ethanol fuel is produced by fermentation of sucrose or glucose in Brazil and produced by corn in the USA, but these raw materials will not be enough to satisfy international demand. The aim of this work was studied the ethanol production from cashew apple juice. A commercial strain of Saccharomyces cerevisiae was used for the production of ethanol by fermentation of cashew apple juice. Growth kinetics and ethanol productivity were calculated for batch fermentation with different initial sugar (glucose + fructose) concentration (from 24.4 to 103.1 g.L-1). Maximal ethanol, cell and glycerol concentrations (44.4 g.L-1, 17.17 g.L-1, 6.4 g.L-1, respectively) were obtained when 103.1 g.L-1 of initial sugar concentration were used, respectively. Ethanol yield (YP/S) was calculated as 0.49 g (g glucose + fructose)-1. Pretreatment of cashew apple bagasse (CAB) with dilute sulfuric acid was investigated and evaluated some factors such as sulfuric acid concentration, solid concentration and time of pretreatment at 121°C. The maximum glucose yield (162.9 mg/gCAB) was obtained by the hydrolysis with H2SO4 0.6 mol.L-1 at 121°C for 15 min. Hydrolysate, containing 16 ± 2.0 g.L-1 of glucose, was used as fermentation medium for ethanol production by S. cerevisiae and obtained a ethanol concentration of 10.0 g.L-1 after 4 with a yield and productivity of 0.48 g (g glucose)-1 and 1.43 g.L-1.h-1, respectively. The enzymatic hydrolysis of cashew apple bagasse treated with diluted acid (CAB-H) and alkali (CAB-OH) was studied and to evaluate its fermentation to ethanol using S. cerevisiae. Glucose conversion of 82 ± 2 mg per g CAB-H and 730 ± 20 mg per g CAB-OH was obtained when was used 2% (w/v) of solid and loading enzymatic of 30 FPU/g bagasse at 45 °C. Ethanol concentration and productivity was achieved of 20.0 ± 0.2 g.L-1 and 3.33 g.L-1.h-1, respectively when using CAB-OH hydrolyzate (initial glucose concentration of 52.4 g.L-1). For CAB-H hydrolyzate (initial glucose concentration of 17.4 g.L-1), ethanol concentration and productivity was 8.2 ± 0.1 g.L-1 and 2.7 g.L-1.h-1, respectively. Hydrolyzates fermentation resulted in an ethanol yield of 0.38 g/g glucose and 0.47 g/g glucose, with pretreated CABOH and CAB-H, respectively. The potential of cashew apple bagasse as a source of sugars for ethanol production by Kluyveromyces marxianus CE025 was evaluated too in this work. First, the yeast CE025 was preliminary cultivated in a synthetic medium containing glucose and xylose. Results showed that it was able to produce ethanol and xylitol at pH 4.5. Next, cashew apple bagasse hydrolysate (CABH) was prepared by a diluted sulfuric acid pre-treatment. The fermentation of CABH was conducted at pH 4.5 in a batch-reactor, and only ethanol was produced by K. marxianus CE025. The influence of the temperature in the kinetic parameters was evaluated and best results of ethanol production (12.36 ± 0.06 g.L-1) was achieved at 30 ºC, which is also the optimum temperature for the formation of biomass and the ethanol with a volumetric production rate of 0.25 ± 0.01 g.L-1.h-1 and an ethanol yield of 0.42 ± 0.01 g/g glucose. The results of this study point out the potential of the cashew apple bagasse hydrolysate as a new source of sugars to produce ethanol by S. cerevisiae and K. marxianus CE025. With these results, conclude that the use of cashew apple juice and cashew apple bagasse as substrate for ethanol production will bring economic benefits to the process, because it is a low cost substrate and also solve a disposal problem, adding value to the chain and cashew nut production